2014
DOI: 10.1016/j.febslet.2014.04.040
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐718 represses VEGF and inhibits ovarian cancer cell progression

Abstract: a b s t r a c tOncogenic activation of VEGF is found in various malignancies, including ovarian cancer. In this study, we investigate the role of microRNA (miRNA) in the regulation of VEGF in ovarian cancer. We find that miR-718 is expressed at low levels and inversely correlates with VEGF expression in ovarian cancer specimens. MiR-718 also directly targets and represses VEGF expression. In addition, miR-718 restoration inhibits ovarian cancer proliferation both in vitro and in vivo. Moreover, VEGF expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…VEGF expression is an independent prognostic factor in EOC patients (20,21). Aberrantly highly expressed VEGF is involved in EOC onset and development, and it regulates diverse biological processes, including cell proliferation, migration, invasion, apoptosis and angiogenesis (21)(22)(23)(24). Hence, VEGF knockdown using miR-655-based targeted therapy may be an effective therapeutic method for patients with EOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF expression is an independent prognostic factor in EOC patients (20,21). Aberrantly highly expressed VEGF is involved in EOC onset and development, and it regulates diverse biological processes, including cell proliferation, migration, invasion, apoptosis and angiogenesis (21)(22)(23)(24). Hence, VEGF knockdown using miR-655-based targeted therapy may be an effective therapeutic method for patients with EOC.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the mechanism underlying the tumour-suppressive roles of miR-655 in EOC, bioinformatics analysis was performed to predict the putative targets of miR-655. VEGF, a well-known oncogene in EOC (20)(21)(22)(23)(24), was a candidate target gene of miR-655 (Fig. 3A).…”
Section: Vegf Is a Direct Target Gene Of Mir-655 In Eoc Cellsmentioning
confidence: 99%
“…Prior reports have suggested that miR-718 is downregulated in ovarian cancer cells and HCC cells (Leng et al, 2014;Sugimachi et al, 2015). miR-718 can exhibit inhibitory effects against ovarian cancer through VEGF repression and it also can suppress cell proliferation in HCC cell lines (Huh7 and PLC/PRF/5) by targeting the HOXB8 gene.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that miRNAs are important in vascular development as well as tumor angiogenesis. In response to hypoxic conditions, tumor cells increase the expression of miRNAs that promote angiogenesis and decrease the expression of miRNAs that repress angiogenesis [35]. For instance, MiRNA-27a and miRNA-126 induce angiogenesis by increasing VEGF and VEGFR expression.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…For instance, MiRNA-27a and miRNA-126 induce angiogenesis by increasing VEGF and VEGFR expression. Conversely, miRNA-15b, miRNA-16 and miRNA-20a/b inhibit angiogenesis by modulating levels of VEGF and VEGFR and are down-regulated in tumor cells [35]. MiRNA-718 represses VEGF expression and its restoration inhibits ovarian cancer cell proliferation in vitro and in vivo [36].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%